Multiple Techno-Functional Characteristics of Leuconostoc and Their Potential in Sourdough Fermentations - Denise C. Müller; Sandra Mischler; Regine Schönlechner; Susanne Miescher Schwenninger (Microorganisms, 2021)
In this study, the potential of Leuconostoc as non-conventional sourdough starter cultures was investigated. A screening for antifungal activities of 99 lactic acid bacteria (LAB) strains revealed high suppression of bakery-relevant moulds in nine strains of Leuconostoc with activities against Penicillium sp., Aspergillus sp., and Cladosporium sp. Mannitol production was determined in 49 Leuconostoc strains with >30 g/L mannitol in fructose (50 g/L)-enriched MRS. Further, exopolysaccharides (EPS) production was qualitatively determined on sucrose (40 g/L)-enriched MRS agar and revealed 59 EPS positive Leuconostoc strains that harboured dextransucrase genes, as confirmed by PCR. Four multifunctional Lc. citreum strains (DCM49, DCM65, MA079, and MA113) were finally applied in lab-scale sourdough fermentations (30 °C, 24 h). Lc. citreum was confirmed by MALDI-TOF MS up to 9 log CFU/g and pH dropped to 4.0 and TTA increased to 12.4. Antifungal compounds such as acetic acid, phenyllactic and hydroxyphenyllactic acids were determined up to 1.7 mg/g, 2.1 µg/g, and 1.3 µg/g, respectively, mannitol up to 8.6 mg/g, and EPS up to 0.62 g/100 g. Due to the observed multifunctionalities and the competitiveness in the natural flour microbiota present in sourdoughs, non-conventional LAB genera such as Leuconostoc seem promising for application in sourdough-based bakery products.